Validity and Practicality of Gamification-Based Lectora Inspire Media: An Interactive Solution for Middle School Students' Mathematics Self-Efficacy - Putri Wahyuni; Ana Yulianti; Sigit Nugroho; Dola Julianti; Oki Candra (CV FOUNDAE, 2025)
Transition to digital learning environments in higher education has highlighted a disconnect between technological adoption and pedagogical effectiveness, particularly in supporting active engagement and learner confidence. Many digital tools focus on content delivery with limited interactivity, resulting in minimal feedback and insufficient support for students’ self efficacy, a key predictor of persistence and performance. This research develops and evaluates an interactive gamified learning medium designed to strengthen instructional quality through structured feedback, challenge mechanics, and learner centered interaction. Effectiveness is defined in three dimensions: improvement in learning outcomes, enhancement of self efficacy, and perceived usability. Using a design and development research framework, the medium was validated by experts, pilot tested, and field tested with undergraduates. Data were collected using instruments on pedagogical quality, achievement, self efficacy, and user experience. Results show high pedagogical validity, meaningful improvement in learning outcomes, and significant enhancement of self efficacy compared with baseline conditions. Usability findings indicate strong perceptions of clarity, engagement, and support for independent learning. The study grounds design decisions in motivation and self efficacy theory and provides empirical evidence for designing pedagogically robust digital learning environments in higher education.